Non-carboxylic Analogues of Aryl Propionic Acid: Synthesis, Anti-inflammatory, Analgesic, Antipyretic and Ulcerogenic Potential - Eissa, S. I.; Farrag, A. M.; Galeel, A. A. A. (Drug Research, 2014)
As a part of ongoing studies in developing new potent anti-inflammatory and analgesic agents, a series of novel 6-methoxy naphthalene derivatives was efficiently synthesized and characterized by spectral and elemental analyses. The newly synthesized compounds were evaluated for their anti-inflammatory activities using carrageenin-induced rat paw edema model, analgesic activities using acetic acid induced writhing model in mice and anti-pyretic activity using yeast induced hyperpyrexia method as well as ulcerogenic effects. Among the synthesized compounds, thiourea derivative (6a, e) exhibited higher anti-inflammatory activity than the standard drug naproxen in reduction of the rat paw edema (88.71, 89.77%) respectively. All of the non-carboxylic tested compounds were found to have promising anti-inflammatory, analgesic and antipyretic activity, while were devoid of any ulcerogenic effects.
Keywords: naproxen; anti-inflammatory; analgesic; antipyretic; ulcer effect